Informal Trade and Underground Economy in Myanmar : Costs and Benefits - Winston Set Aung (Institut de recherche sur l'Asie du Sud-Est contemporaine, 2011)
At present, collecting and analyzing data from inside Myanmar remains notoriously difficult. There is, therefore, a non-Myanmar approach towards the majority of studies on Myanmar. This is especially the case when dealing with informal or illegal trade within the country's territory. IRASEC and the Observatory on Illicit Trafficking wanted to fill this gap by giving the floor to Professor Winston Set Aung, the founder and the director of the Asia Development Research Institute, and director of the Asia Language and Business Academy in Myanmar. He is also an MBA lecturer at the Institute of Economics in Yangon and is involved in several international and regional research programs in partnership with various research institutes including the Institute of Asian Studies, Chulalongkorn University, Thailand; Tokyo University, Japan; and the Institute for Security and Development Policy of Sweden, Stockholm Environmental Institute. The focus of Professor Winston Set Aung's study is to provide a Myanmar-centric perspective on informal or illegal trade. The author offers an analysis regarding the process of informal exchanges through a pragmatic and non-contextualized critique. The causes of informal and illegal exchanges are identified and described without commenting on their origins. This intentional, measured, and calculated conservative perspective enables us to think on how to best use these flows in the current political situation in Myanmar. It seems therefore useful and relevant to make this data available to our readers.